Reduced Apparent Diffusion Coefficient in Various Brain Areas following Low-Intensity Transcranial Ultrasound Stimulation - Yuan, Yi; Dong, Yanchao; Hu, Shuo; Zheng, Tao; Du, Dan; Du, Juan; Liu, Lanxiang (Frontiers in Neuroscience, 2017)
Diffusion of water molecules closely related to physiological and pathological information of brain tissue. Low-intensity transcranial ultrasound stimulation (TUS) has advantages of noninvasive, high spatial resolution and penetration depth. Previous studies have demonstrate that TUS can modulate neuronal activity and alter cortical hemodynamic. However, how TUS affect diffusion of water molecules remain unclear. In this paper, in order to evaluate the effect of low-intensity TUS on the diffusion of water molecules in brain tissue, diffusion-weighted magnetic resonance (MR) imaging was performed in nineteen healthy Sprague-Dawley rats in sham surgery group (six rats) and TUS group (thirteen rats) Subsequently, rats were stimulated by low-intensity transcranial ultrasound for 5 minutes in TUS group. Finally, rats of sham surgery group and TUS group were imaged again by diffusion-weighted MR imaging. The apparent diffusion coefficient (ADC) was measured in caudate putamen region and middle brain motor-related region of each rat in sham surgery group and TUS group. Surgery-related and TUS-related changes were calculated using a statistical analysis. The mean ADC values of marked regions of six rats in sham surgery group were 0.743 ± 0.031 (pre-surgery) and 0.745 ± 0.029 (post-surgery). The mean ADC values of marked regions of thirteen rats in TUS group were 0.749 ± 0.032 (pre-TUS) and 0.712 ± 0.033 (post-TUS) Compared to the pre-TUS values, the mean ADC values of the rats decreased 4.9% (*P<0.05) post-TUS. These results of this study demonstrate that low-intensity TUS can restrict the diffusion of water molecules in brain tissue.